Implementasi Kebijakan Program Gotong Royong (Studi di Kecamatan Bukit Kecil Kota Palembang) - Permata, Amira Intania (Universitas Batanghari Jambi, 2024)
This study discusses the implementation of the gotong royong program policy in Bukit Kecil Sub-district, Palembang City, South Sumatra Province. Keeping the environment clean is very important in an effort to maintain health and prevent disease. The gotong royong program is one way to increase public awareness in maintaining environmental cleanliness. The principle of gotong royong reflects collaboration between residents in maintaining the cleanliness and aesthetics of the environment where they live. In the theoretical foundation, this study refers to Edward III's theory to understand the process of public policy implementation and the factors that influence it. This theory helps understand communication, disposition, and implementation decisions in the context of the gotong royong program. The research technique used is qualitative, where the main data is collected through interviews with Mr. Untung Sobirin, who serves as the Head of General Services in Bukit Kecil Sub-district. Additional information was obtained from analyzing related literature as secondary data. The results showed that the implementation of gotong royong was conducted every Sunday morning with active participation from the community, local government, and echelon 2 officials. The socialization of the gotong royong program is considered successful, although there are still obstacles such as the indifference of some residents. The availability of waste disposal sites (TPS) reflects a commitment to keeping the environment clean.